RESECTABILITY RATES IN LOCALLY ADVANCED ESOPHAGEAL CARCINOMA FOLLOWING NEO-ADJUVANT CHEMO-RADIOTHERAPY - Abbas, Asad; Ali, Nasir; Hameed, Shahid; Shah, Mazhar Ali (Journal of Ayub Medical College Abbottabad, 2003)
Background: Purpose of this study was to assess the resectability rates in un-resectable (Stages III and IV) cancers of the esophagus, to assess the complete pathological response and to compare the efficacy between two chemotherapy regimens. Methods: From January 1999 to June 2002, medical records of the patients with un-resectable esophageal cancers were reviewed, who received radiation-therapy with concomitant chemotherapy using following regimens:- Arm A:- 5FU 500 mg/m2 intravenous push (IVP) on first 5 and last 5 days of radiation. Arm B:- 5FU 1 Gm/ m2/Day 96 hour continuous infusion (CIV) and Cisplatin 70 mg/ m2 on day one and twenty eight of radiation. At completion of neoadjuvantchemo-radiation patients were offered surgery after four to six weeks. Results: 35 patients had un-resectable esophageal cancer. Twenty-six received arm A, and 9 arm B treatment. Of 26 patients in arm A, in 13 the disease was made resectable and two of them showed complete pathological response in surgical specimen, thirteen had progressive disease. On the other hand, of 9 patients receiving arm B treatment, in 7 the disease was made resectable and out of them 5 showed complete pathological response in surgical specimen and two had progressive disease. Conclusion: Resectability in patients receiving arm B treatment was better than the patients treated arm A. The data is not mature enough to assess the effect on disease free survival or overall survival, this will be seen and published later. Keywords: Un-resectable esophageal cancer, neo-adjuvant chemoradiation